Information Needs for Climate Change Adaptation among Farmers of Uttrakhand, India (Indian Journal of Extension Education, 2018)
The study attempts to determine the information needs for climate change adaptation and preferenceof farmers aboutcommunication media and methods in the hilly region of Uttarakhand. Using the multistage sampling procedure, a total of 300 men and women farmers were selected through Probability Proportionate to Size method from the villages. Pretested interview schedule was used for collecting the information. The findings show that the major areas of information needs of farmers on adaptation strategies to climate change werewater harvesting schemes,crop management strategies, drought/flood tolerant crop varieties, control of animal diseases, climate change tolerant livestock breeds, quality of feed/fodder, sources for credit, climate-smart agriculture practices and technology andinsurances.It was also found that farm and home visit was the most preferred method to receive information. Extensive efforts along with the application of emerging information communication technologies for the information-oriented farming community are required in order to impart information to farmers related to climate change adaptations.